Cognitive flexibility, heart rate variability, and resilience predict fine‐grained regulation of arousal during prolonged threat. (22nd February 2016) - Hildebrandt, Lea K.; McCall, Cade; Engen, Haakon G.; Singer, Tania
Abstract: Emotion regulation in the ongoing presence of a threat is essential for adaptive behavior. Threatening situations change over time and, as a consequence, require a fine‐tuned, dynamic regulation of arousal to match the current state of the environment. Constructs such as cognitive flexibility, heart rate variability, and resilience have been proposed as resources for adaptive emotion regulation, especially in a moment‐to‐moment fashion. Nevertheless, none of these constructs has been empirically related to the dynamic regulation of arousal as it unfolds over the course of a prolonged threatening episode. Here, we do so by placing participants in a threatening and evolving immersive virtual environment called Room 101, while recording their skin conductance. Subsequently, participants rated their subjective arousal continuously over the course of the experience. Participants who had shown greater cognitive flexibility in a separate task (i.e., fewer task‐switching costs when switching to evaluating the valence of positive stimuli) showed better regulation of physiological arousal (skin conductance level), during less‐threatening phases of Room 101. Individuals with higher trait resilience and individuals with higher resting heart rate variability showed more regulation in terms of their subjective arousal experience. The results indicate that emotional, cognitive, and physiological flexibility support nuanced adaptive regulation of objective and experienced arousal in the ongoing presence of threats. Furthermore, the results indicate that these forms of flexibility differentially affect automatic and objective versus reflective and subjective processes.